Comparative Efficacy of Clomiphene Citrate and Letrozole in Treating Infertility in Women with Polycystic Ovary Syndrome - Shafia Afridi, Asma Ambareen, Shagufta Naz, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the efficacy of Clomiphene Citrate and Letrozole in inducing ovulation and pregnancy rates in women with Polycystic Ovary Syndrome (PCOS). Methodology: A retrospective study was conducted at Civil Hospital, Dara Adam Khel, Merged Area Kohat, Pakistan, from November 2020 to April 2021. A total of 80 women diagnosed with PCOS were randomly assigned to receive either Clomiphene Citrate (n=40) or Letrozole (n=40). The primary outcome was ovulation rate, and secondary outcomes included pregnancy rates, clinical pregnancy rates, and endometrial thickness. Statistical analysis was performed using independent t-tests, and a p-value of <0.05 was considered statistically significant. Results: The ovulation rate was significantly higher in the Letrozole group (90%, n=36) compared to the Clomiphene Citrate group (80%, n=32) with a p-value of 0.0133. Pregnancy rates were 45% (n=18) for Letrozole and 35% (n=14) for Clomiphene Citrate (p=0.062). Clinical pregnancy rates were similar between groups (17.5% vs 22.5%, p=0.419). No significant differences were observed in endometrial thickness (Letrozole: 9.2mm vs Clomiphene Citrate: 8.4mm, p=0.834). Conclusion: Letrozole was more effective than Clomiphene Citrate in inducing ovulation in women with PCOS, although pregnancy rates were similar between the two treatments. These findings suggest that Letrozole should be considered a first-line treatment for ovulation induction in PCOS patients, with further studies needed to assess long-term fertility outcomes. Keywords: Polycystic Ovary Syndrome, Letrozole, Clomiphene Citrate, Ovulation Induction, Infertility.